Cognitive and linguistic profile of Greek speakers with parkison's disease - Anyfantis, Emmanouil (My University, 2022)
Parkinson's disease (PD) is a progressive neurodegenerative disease that is characterized by movement-related (motor) symptoms. In addition to motor symptoms, recent research has investigated the role of non-motor symptoms in PD such as cognitive and language disturbances. A growing number of studies suggest that language deficits are common in individuals with PD in the early stages of the disease. The literature has documented language disorders characteristic of PD progression in several different languages. However, a limited number of studies have explored the cognitive-linguistic profile of Greek-speaking individuals with PD. The main aim of the research reported in this thesis was to explore cognitive and language deficits in non-demented Greek-speaking individuals with idiopathic PD. For this purpose, the cognitive and language abilities of a group of 24 participants with PD were compared with that of 15 healthy controls matched for sex, age and education. A set of neurocognitive and language measures were administered. The neurocognitive tasks included attention span, verbal working memory, set-switching, executive functions, and semantic memory. The language tasks included a confrontation naming task of nouns and verbs, a sentence repetition task, and a metaphor processing task. The results revealed that the PD group performed significantly lower on executive functions tasks (i.e., Trail making Test-A and B, and phonemic fluency) compared to healthy controls. However, no significant difference was observed between the two groups on verbal working memory measures and semantic fluency. Regarding the language tasks, the results showed that the PD group had greater difficulty in retrieving nouns and verbs and processing metaphors and idioms compared to healthy controls. No significant difference was found on a sentence repetition task. Moreover, the effect of instrumentality and verb-noun name relation on action naming ability in the PD group was explored. The Greek Object and Action Test (GOAT) a picture-based assessment of common nouns and verbs was administered. Two types of verbs were tested. This included semantically complex "heavy" verbs (i.e., instrumental verbs e.g., "sweeping") and semantically "light" verbs (i.e., non-instrumental verbs e.g., sitting). The PD group performed better on naming instrumental verbs than non-instrument indicating that instrumentality has a positive effect on verb naming. V Multiple regression analyses revealed that the neurocognitive variables of set switching and working memory and the psycholinguistic factor of picture complexity predicted the verb naming accuracy. This is the first study exploring the cognitive-linguistic profile of Greek-speaking individuals with PD. The results are consistent with the findings of previous studies that revealed language disorders in this population. Future clinical studies with larger PD samples should combine neurocognitive, linguistic and neuroimaging testing to further explore the cognitive-linguistic profile of PD in the early stage so that speech pathologists can determine evidence-based treatment options.
Keywords: metaphor processing; Greek language; Parkinson's disease; instrumentality; word retrieval deficits; sentence processing